(untitled) (Educational Dimension, 2020)
The article describes the peculiarities of the monitoring systems of higher education quality in Ukraine and Germany at the present stage, taking into account the national traditions, historical experience and mentality of the population, also enshrined at the legislative level. The impact of public administration in the field of education and independent public organizations (agencies) on the nature and quality of monitoring procedures should be evaluated, since the involvement of society in monitoring the quality of higher education should be an integral part of a full-fledged education system. Given the specifics of the step-by-step system for regional monitoring of the quality of higher education in Germany, the role of the Conference of Rectors of Higher Education Institutions in this issue was demonstrated. Recent years’ statistics are used to illustrate the polarity of Ukrainian and German universities positions in world rankings (for example, The Times Higher Education World University Rankings and World University Rankings). The results of a comparative analysis of the approaches to higher education quality assurance and monitoring in Germany and Ukraine, the activities of monitoring entities in the two countries at all levels, starting from the national level and ending with the level of the educational institution, are presented in a summary table. The table demonstrates also the conceptual and functional components of quality monitoring: the purpose of the monitoring, the objects of monitoring, the levels and entities, the public initiative, the priority of the monitoring levels, the dominant principles, the overall orientation and monitoring of the quality of higher education. The article outlines the prospects of using elements of the progressive international experience of organizing a monitoring system of higher education quality to reform the national higher school, which is a necessary step in the process of its entry into the European Higher Education Area.